Die Politik des Waldes - Pülzl, Helga (2010)
The thesis deals with the question of why no international legally binding instrument for forest policy exists so far. The thesis shows that the problem definition presents a form of control for the decision making process and for the problem solution. Therefore, it is demonstrated how locations, reports and non-human objects are related to the development of international forest policy within United Nations. In the development of international forest policy, the policy problem was framed as "deforestation and degradation of tropical forests". In the second phase of policy formulation, the "deforestation and degradation of all forests" moves to the centre of interests. The thesis analyses furthermore the formation of meaning of the policy narratives that are intertwined with international forest policy. The identification of global environmental discourses that transfer a certain kind of meaning of policy and of problem solution, that operate with discursive practices and technologies of power, and that use rhetorical devices, allows to show which rules and practices influence how natural resource policy arises. In this way it can be shown how policy problems come into being and how they are understood. Furthermore, it allows identifying policy change in a non-decision-making process.